Seroprevalence of SARS‐CoV‐2 in Utsunomiya City, Greater Tokyo, after the first pandemic in 2020 - Nawa, Nobutoshi; Kuramochi, Jin; Sonoda, Shiro; Yamaoka, Yui; Nukui, Yoko; Miyazaki, Yasunari; Fujiwara, Takeo (Journal of general and family medicine, 2021)
Background A seroepidemiological study was conducted on a random sample of households in Utsunomiya City, Tochigi Prefecture, Greater Tokyo, Japan, to assess the seroprevalence of SARS‐CoV‐2. Methods The level of IgG antibodies in the blood of the recruited subjects was assessed using chemiluminescence immunoassay analysis. In addition, the population‐based prevalence of SARS‐CoV‐2 was estimated. Results Three positive afebrile cases were confirmed. The estimated unweighted prevalence and weighted prevalence of SARS‐CoV‐2 infection were 0.40% and 1.23%, respectively. Conclusions This study suggests that the prevalence of SARS‐CoV‐2 may have been underestimated. Wider testing strategies may lead to revealing more SARS‐CoV‐2 cases. We conducted a seroepidemiological study in a random sample in the Greater Tokyo area. IgG antibody level for SARS‐CoV‐2 in the blood was quantitatively assessed. We estimated the population‐based prevalence using data from basic resident registry. The unweighted prevalence and weighted prevalence of COVID‐19 were 0.40% and 1.23%, respectively.